(untitled) (Academia Journal of Medicine, 2020)
Background: Long-term damage and malfunction of various organ systems can be linked to diabetes and its related complications. The objective is to evaluate the microvascular and macrovascular complications of Type 2 Diabetes Mellitus. Subjects and Methods: Patients with confirmed diabetes attending OPD were included. A detailed history is recorded for each individual case with diabetes mellitus, obesity, symptoms and family history with individuals suffering from diabetes mellitus. The physical examination was done for sensory and motor signs. Prevalence rates were typically calculated and standardized for age and sex for microvascular and macrovascular complications at baseline. Results: The overall number of patients examined was 100, of which 54% were male and 46% were female. The mean age of the patients in the sample was 53 years. The prevalence of diabetes increased with age. The prevalence of diabetes in elderly patients was maximum for 61 to 70 years of age. 29 percent of patients have a positive history of diabetes in the family. 13% of patients were smokers and all of them were males. The risk factor – Hypertension –19%, Obesity – 25% and hypercholesterolemia – 43% were present at the time of diagnosis. Conclusion: The general risk of microvascular and macrovascular problems is severe in patients with type 2 diabetes that are relatively early in the disease phase. Such findings indicate that the early risk factor may be actively changed, especially in regions with a high prevalence of complications. There are important correlations between predominant diabetes and the rising circumference and body mass index. Coronary artery disease, nephropathy and retinopathy have become particularly prevalent.